Buster Keaton - Silent Classics, 1 - Keaton, Buster; Cline, Edward F.; Lessley, Elgin; Roberts, Joe; Seely, Sybil (starmedia, 2006)
Buster zieht um (1922): One of Buster Keaton's best short films ever, "Cops" is a fine showcase of Keaton's physical comedy. A series of mishaps gets him deeper and deeper into trouble, culminating in what appears to be the entire world's police force chasing after him. Keaton's efforts to elude them are both inventive and funny. This short also contains a classic sequence with a horse and an overfull wagon load of furniture. [www.rinkworks.com]